Elimination of gender-related employment disparities through statistical process control - Mary E. Graham; Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2008)
This paper proposes a novel approach that has the potential to hasten the eradication of gender disparities in employment. This approach relies upon the concept of statistical process control (SPC) to more systematically remedy disparate employment outcomes for women. SPC also serves as a new vehicle for conceptualizing the influence of industry on equal employment opportunity (EEO) outcomes. Using data from U.S. Current Population Surveys, we compare industries on EEO performance as assessed by a recently developed Systemic Gender Disparity Scorecard. The theory and practice of SPC suggest that further improvement, and by far the greater opportunity for gender-related EEO progress, necessitates fundamental changes in each industry's practices and norms that serve as barriers to gender parity. We recommend more resources to support collaboration between employers and EEO enforcement agencies.
Keywords: J78; M12; 330; equal employment opportunity; statistical process control; discrimination; wage differentials